2019
DOI: 10.5935/0004-2749.20190030
|View full text |Cite
|
Sign up to set email alerts
|

A case of late-onset capsular block syndrome and its surgical treatment

Abstract: Capsular block syndrome is a rare complication of phacoemulsification surgery with continuous curvilinear capsulorhexis and intraocular lens implantation. Here, we report a case of very late-onset capsular block syndrome that developed 13 years after cataract extraction and present the surgical approach used for its successful treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…And third, having the associated symptoms of recurrent mild pain, photophobia, and redness with the dramatic resolution of these symptoms after the surgical management. To the best of the author's knowledge, up to date, there is only one reported case that described CBDS development after 14 years [ 4 ], and only two described it after 13 years (as in our patient) [ 8 , 9 ]. Upon careful examination of the anterior segment with maximal dilation, it was noted that the capsulorhexis of the OS was small (4.7 mm) compared to the OD (5.5 mm), which explains the unilateral involvement in our case.…”
Section: Discussionmentioning
confidence: 90%
“…And third, having the associated symptoms of recurrent mild pain, photophobia, and redness with the dramatic resolution of these symptoms after the surgical management. To the best of the author's knowledge, up to date, there is only one reported case that described CBDS development after 14 years [ 4 ], and only two described it after 13 years (as in our patient) [ 8 , 9 ]. Upon careful examination of the anterior segment with maximal dilation, it was noted that the capsulorhexis of the OS was small (4.7 mm) compared to the OD (5.5 mm), which explains the unilateral involvement in our case.…”
Section: Discussionmentioning
confidence: 90%
“…described a technique of injecting dispersive ophthalmic viscosurgical device (OVD) between the IOL and the posterior capsule to displace the milky CBS fluid into the anterior chamber, then removing both the OVD and CBS fluid with an irrigation/aspiration handpiece. [ 19 ] Nd: YAG laser capsulotomy was performed thereafter to prevent CBS recurrence. [ 19 ] Needle aspiration of the CBS fluid by inserting the needle through the anterior capsule between the IOL and posterior capsule via a corneal or scleral tunnel, followed by removal of adherent anterior capsular fibrosis and irrigation and aspiration has also been described.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Nd: YAG laser capsulotomy was performed thereafter to prevent CBS recurrence. [ 19 ] Needle aspiration of the CBS fluid by inserting the needle through the anterior capsule between the IOL and posterior capsule via a corneal or scleral tunnel, followed by removal of adherent anterior capsular fibrosis and irrigation and aspiration has also been described. [ 12 , 13 ] In our case where the patient presented 16 years postcataract surgery, release of the IOL from the fibrotic anterior capsule would have been challenging with either of these techniques, with inherent risks of inadvertent capsular bag tear or rupture and IOL damage from the needle.…”
Section: Discussionmentioning
confidence: 99%
“…Gilhotra et al 18 and Koh et al 25 reported recurrence of CBS 1 week and 10 months after YAG capsulotomy, respectively. Capsular fluid aspiration 5,6,26 and vitrectomy 7,12 can be performed if laser treatment fails 7 for refractory cases, or cases that need specimens for analysis. All our patients, no matter which type in anterior segment OCT, received laser capsulotomy without complications, and mean visual acuity improved by 0.18 ± 0.10 on the LogMAR.…”
Section: Discussionmentioning
confidence: 99%